2017
DOI: 10.1113/jp275089
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced skeletal muscle regrowth and remodelling in massaged and contralateral non‐massaged hindlimb

Abstract: Key pointsr Muscle fibre cross sectional area is enhanced with massage in the form of cyclic compressive loading during regrowth after atrophy.r Massage enhances protein synthesis of the myofibrillar and cytosolic, but not the mitochondrial fraction, in muscle during regrowth. r Massage in the form of cyclic compressive loading is a potential anabolic intervention during muscle regrowth after atrophy.Abstract Massage, in the form of cyclic compressive loading (CCL), is associated with multiple health benefits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(130 citation statements)
references
References 63 publications
7
117
5
Order By: Relevance
“…Interestingly, they also found that the contralateral non-massaged limbs exhibited a comparable 17% higher muscle fiber size compared to reloading alone suggestive, as formerly observed for other markers, of a systemic effect of CCL. The authors indicate that the mechanism could, at least in part, be mediated by the presence of Pax7+ cells induced by the CCL treatment [67].…”
Section: Effects Of Mt In Muscle Regenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, they also found that the contralateral non-massaged limbs exhibited a comparable 17% higher muscle fiber size compared to reloading alone suggestive, as formerly observed for other markers, of a systemic effect of CCL. The authors indicate that the mechanism could, at least in part, be mediated by the presence of Pax7+ cells induced by the CCL treatment [67].…”
Section: Effects Of Mt In Muscle Regenerationmentioning
confidence: 99%
“…The study was based on the observation that skeletal muscle and satellite cells are sensitive to biophysical micro environmental cues, such as mechanical loading and stretch-associated progenitor activation [66,67]. The treatment consisted on stimulations at 1 Hz for 5 minutes every 12 h by approaching and retracting a magnet to the tibialis anterior muscle subcutaneously implanted ferrogel on a murine model of myotoxin-induced or hind limb ischemia.…”
Section: Effects Of Mt In Muscle Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, the group led by David J. Moone evaluated the regeneration of severely injured muscle by cyclic mechanical compressions driven by the combined use of external magnets and biphasic ferrogels, as an alternative mode to delivering a variety of growth factors, such as insulin-like growth factor or IGF, fibroblast growth factor-2 or FGF-2, among others [ 44 , 67 ]. The study was based on the observation that skeletal muscle and satellite cells are sensitive to biophysical micro-environmental cues, such as mechanical loading and stretch-associated progenitor activation [ 45 , 68 ]. The treatment consisted of stimulations at 1 Hz for 5 min every 12 hr by approaching and retracting a magnet to the tibialis anterior muscle subcutaneously implanted ferrogel on a murine model of myotoxin-induced or hind limb ischemia.…”
Section: Molecular Determinants Of Mt: Lessons From Animal Models mentioning
confidence: 99%